The mediating role of organizational indifference in the relationship between job burnout and administrative health of education staff in Tabriz - Javad Mehraban (Institute of Management fekrenoandish, 2021)
Extended Abstract Abstract Human resources, loyal to and consistent with the goals and values ​​of the organization, that operate beyond the duties set in their job description, are important factors in organizational effectiveness. The aim of this study was to investigate the relationship between occupational burnout and administrative health of employees with the mediating role of organizational indifference. The research method was descriptive-correlation. Subjects were selected by simple random sampling. In the present study, the standard questionnaires of occupational burnout of Tommy et al. (1999), organizational indifference of Danaeifard et al. (2010), and administrative health of Hui and Fieldman (1996) were used. Their validity and reliability were confirmed respectively by academic experts and Cronbach's alpha coefficient test. Structural equation technique was used to analyze the data using Lisrel statistical software and Spss statistical software. Quantitative findings of the research hypothesis test showed that there is a negative and significant relationship between job burnout and organizational indifference with employees' administrative health, and organizational indifference has a mediating role in the relationship between job burnout and office health. Introduction A factor that has been identified as effective on organizational outcomes in the career path is the phenomenon of job flattening. According to many researchers, job burnout has quickly become a critical issue for organizations and therefore requires proper management to avoid employee dissatisfaction. For this reason, job burnout is a growing concern and has negative consequences such as decreased job satisfaction, decreased satisfaction of career path and increased willingness to leave employees (Karami, Mohammadesmaeili, & Hajiasgari Nooshabadi, 2020). Over the past decade, most organizations have witnessed re-engineering of organizational structure. To stay competitive, organizations strive to be more efficient by flattening organizational structures and rebuilding the process. Fewer promotion opportunities for employees is the result of Reorganization. Thus, many employees experience flattening (Shabeer, Mohammed, Jawahar, & Bilal, 2019). According to Starrald (2010), recent research shows that there are either not motivation and willing to work in 90% of employees or their behavior is not in line with the goals of the organization. One of the main causes is indifference (Lamb, Maire, & Doecke, 2017). The past, present and future is the same for those who suffer from such a phenomenon, which makes them become indifferent to the future (Ghazifar & etal, 2019). In another approach, organizational indifference is a situation in which employees do not engage themselves in organizational success, work only to get paid and not be fired, and never look for opportunities for the growth of their organization (Karimi & etal, 2019). In this regard, attention to the relationship between organizational indifference and administrative health appears to be very important. Research on the relationship between organizational indifference and office health has shown that there is a negative and significant relationship between them (Su, Kuo, Cheung, Hung, & Cheng, 2017). In the present study, an attempt has been made to investigate this relationship. Therefore, management experts believe that the management, growth and development of human resources depend on the selection and proper use of human resources in jobs and organizational positions. And because there are many shortcomings and deficiencies in administrative system structure in the education offices in this regard, Due to the centrality of the organizational mission, which is study and research, this research was conducted in order to determine the position of administrative health in the organization. For this purpose, this study begins with the question of whether there is a relationship between job burnout and staff health with regard to the mediating role of organizational indifference in the staff of education departments in Tabriz. Case study In this study, all employees of education departments in Tabriz participated; and it has been examined as a case study. Theoretical framework Indifference to the manager includes behaviors on the part of employees in which employees refuse to comment on their abilities in order not to take on more responsibility, do not inform the manager about their work process, and sometimes procrastinate and deliberately ignore their manager's wishes, or sometimes resort to expedient lies to avoid responding (Kramer, 2006). Indifference to the organization refers to the condition in which the staff do not engage in the organization's success or failure, They have no attachment to the organization (Nasre Esfahani, Ghorbani, Amiri, & Farokhi, 2013). Indifference to the client is a condition in which employees limit client service to a certain time during office hours (Leander, 2009). Indifference to co-workers is that employees do not cooperate in group work and refuse to make friendship with others (Willemsen, Keren, 2009). Indifference to work refers to situations in which employees are not careful enough in their work, have no creativity and innovation in work and consider organizational tasks as worthless (Na sre Nasre Esfahani & etal, 2013).Zhang & Frenkel (2018) conducted a study on the issue of indifference and laziness of employees. The results indicated that the misconductiong managers are the reason for the staff's unusual behavior and eventually their disappointment by inducing indifference in them (Zhang&Frenkel, 2018). Methodology This study was a descriptive-correlational study. The study population included all employees of education departments of Tabriz in 677 people. According to Krejcie and Morgan table, 245 people are included in this study as a sample. The sampling method was simple random. Valid job plateau (Tammy, 1999), organizational indifference (Danaeifard, Hasanzadeh, Salarieh, 2010) and administrative health questionnaires (Hoyand Feldman, 1987) were used to collect data. The validity of the questionnaires was confirmed by expert professors. And their reliability was confirmed by Cronbach's alpha coefficient test., The structural equation technique was used in order to analyze the data, using Lisrel statistical software and Spss statistical software.   Discussion and Results In the first hypothesis: the strength of the relationship between job burnout and organizational indifference of employees was calculated equal to (0.73), which indicates a favorable correlation. The t-test of the test (10.68) was obtained which is greater than the critical value of t at the 5% error level (1.96) and shows that the strength of the observed relationship is significant. Hypothesis 2: The strength of the relationship between organizational indifference and employees' administrative health was calculated equal to (-0.65), which indicates a favorable correlation. The t-test of the test (8-22) was obtained which is less than the critical value of t at the level of 5% error (i.e. -1.96) and shows that the strength of the observed relationship is significant. Therefore, it can be said that there is a negative and significant relationship between organizational indifference and employees' administrative health. Hypothesis 3: The strength of the relationship between job burnout and employees' administrative health was calculated equal to (-0.39), which indicates a favorable correlation. The t-test of the test (-2.32) was obtained which is less than the critical value of t at the 5% error level (i.e. -1.96) and shows that the strength of the observed relationship is significant. Therefore, it can be said that there is a negative and significant relationship between job burnout and office health of employees. Hypothesis 3: The direct effect of the two structure with the indirect effect of the interfered variable of organizational indifference should be investigated in order to examine the mediating effect of organizational indifference in the topic under discussion, so that if the effect increases, the mediating effect of organizational indifference can be considered acceptable. In the present hypothesis, the strength of the direct relationship between job burnout and office health is (-0.39).